HAK ATAS KEKAYAAN INTELEKTUAL, HAK MEREK, RAHASIA DAGANG, DAN PELANGGARAN HAK MEREK DAN RAHASIA DAGANG SERTA HAK PATENT (LITERATUR REVIEW ARTIKEL - Maulidda Hafsari, Yuliana (Dinasti Review Publisher, 2021)
Indonesia as a developing country that is rich in natural, artistic and cultural resources has a variety of traditional knowledge that requires legal recognition and protection that is able to maintain the ownership of traditional knowledge as the nation's internationally recognized work. Regulations in the case of intellectual property rights, particularly the patent law, aim to provide legal protection for the invention of intellectual works to the inventors and provide economic benefits for the results of their inventions. However, the patent law which adopts IPR in developed countries in its implementation, has not been able to provide recognition and protection to traditional knowledge optimally. This is due to differences in the concept of intellectual property rights that are exclusive, and individuals with traditional knowledge that have traditional, communal and open characteristics. The lack of public understanding of IPRs as well as inadequate mastery of technology and minimal budget are also obstacles to traditional patenting of knowledge. Pemerintah RI mengundangkan UU No.21 Tahun 1961 tentang merek perusahaan dan merek perniagaan ( UU merek 1961 ) untuk menggantikan UU merek kolonial Belanda. UU merek 1961 merupakan undang-undang indonesia pertama di bidang HAKI. Berdasarkan pasal 24, UU No.21 Tahun 1961 , yang berbunyi “ Undang-undang ini dapat disebut undang-undang merek 1961 dan mulai berlaku satu bulan setelah undang-undang ini diundangkan “. Undang-undang tersebut mulai berlaku tanggal 11 November 1961. Penetapan UU merek 1961 dimaksudkan untuk melindungi masyarakat dari barang-barang tiruan/bajakan.